1997
DOI: 10.1103/physrevb.56.1593
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution photoemission from a tunable quantum well: Cu(111)/Na

Abstract: High-resolution photoemission (⌬Eϭ5 meV) at a low photon energy ͑3.82 eV͒ is used to probe discrete quantum-well-type subband states near, below, and above E F for Cu͑111͒ covered with 2 ML or less of Na. A subband characteristic of the monolayer range shifts gradually to lower energy as the coverage is increased, extending below the Fermi level for coverages above 0.85 ML. Combined with previous observations of shifts for filled and empty states the present results show that the Na monolayer has continuously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 27 publications
4
63
1
Order By: Relevance
“…Intriguingly, the binding energies of the QWS are strongly affected by the Na coverage [151]. For example, for coverages of 1 and 0.95 monolayers, binding energies of À127 and À42 meV with respect to the Fermi level were observed with scanning tunneling spectroscopy [181] confirming previous data from photoelectron spectroscopy [151] which yielded values of approximately À100 and À75 meV. For the lanthanides Lu, Ho and Gd, Bauer et al observed nearly symmetric spectral lines (rather than bands with a sharp onset), presumably due to the large effective mass of the surface states on these surfaces [195].…”
Section: Spectroscopy Of ''Perfect'' Surfacesmentioning
confidence: 99%
See 4 more Smart Citations
“…Intriguingly, the binding energies of the QWS are strongly affected by the Na coverage [151]. For example, for coverages of 1 and 0.95 monolayers, binding energies of À127 and À42 meV with respect to the Fermi level were observed with scanning tunneling spectroscopy [181] confirming previous data from photoelectron spectroscopy [151] which yielded values of approximately À100 and À75 meV. For the lanthanides Lu, Ho and Gd, Bauer et al observed nearly symmetric spectral lines (rather than bands with a sharp onset), presumably due to the large effective mass of the surface states on these surfaces [195].…”
Section: Spectroscopy Of ''Perfect'' Surfacesmentioning
confidence: 99%
“…2 For Na overlayers on Cu(1 1 1) STS measurements have been performed for energies below as well as above E F [181]. Intriguingly, the binding energies of the QWS are strongly affected by the Na coverage [151]. For example, for coverages of 1 and 0.95 monolayers, binding energies of À127 and À42 meV with respect to the Fermi level were observed with scanning tunneling spectroscopy [181] confirming previous data from photoelectron spectroscopy [151] which yielded values of approximately À100 and À75 meV.…”
Section: Spectroscopy Of ''Perfect'' Surfacesmentioning
confidence: 99%
See 3 more Smart Citations